IMPROVING VOCABULARY MASTERY USING INTERACTIVE WORD WALLS METHOD: A CASE OF SEVENTH GRADE IN SMP IT AL FIKRI SEMARANG - Christina Ayunda Raras Christina; Wahyu Widianto; Rahmawati Sukmaningrum (STKIP Subang, 2023)
This research is based an a study which attempts to examine the use of the word wall method in improving vocabulary for 7th grade students of SMP IT Al Fikri Semarang. The purpose of this research was to find out the word wall method in improving students vocabulary. The objectives of this study are (1) To find out the extent of students’ vocabulary achievement before using the interactive word walls method, (2) To find out the extent students’ vocabulary achievement after using the interactive word walls method, (3) To find out whether there is an improve student’s English vocabulary through interactive words walls method achievement significantly. Pre-experimental research was used in this study method. In this study, the writer collects the data by using the tests. The writer uses the statistical calculation with SPSS in data analyzed. The sample of this research is one class from 7th. The class has 20 students. As a results , it can b witnessed from the mean of pre-test and post-test. In pre-test result is 57. After being given treatment,the post-result is 68. Moreover, the hypothesis result showed that Ha is accepted. Because, T-value was higher than the table’s critical value (2.447 > 2.109), it indicates that there was a significantly improving vocabulary using word wall method.